External influences in the emergence of Islamic mysticism from Nicholson's point of view - Ali Hussein Gahat Al-Abduli, Abdul Radha Hasan Chyad Al-Hussainawi, (Opción, 2019)
The aim of the study is to investigate the external influences in the emergence of Islamic mysticism from Nicholson's point of view via comparative qualitative research methods. As a result, the differences of opinion in the creation of Islamic mysticism to the origins of the mystics of the mystical sports have been practiced by the mystic during his worship. The Islamic mysticism is no different from Sufism in other nations in terms of spiritual sports. In conclusion, Islamic mysticism has met a number of internal factors of the Islamic religion, and the external influences were mentioned earlier in its inception